Attention training modulates resting-state neurophysiological abnormalities in posttraumatic stress disorder. (30th January 2018) - Badura-Brack, Amy; McDermott, Timothy J.; Becker, Katherine M.; Ryan, Tara J.; Khanna, Maya M.; Pine, Daniel S.; Bar-Haim, Yair; Heinrichs-Graham, Elizabeth; Wilson, Tony W.
Abstract: Recent research indicates the relative benefits of computerized attention control treatment (ACT) and attention bias modification treatment (ABMT) for posttraumatic stress disorder (PTSD); however, neural changes underlying these therapeutic effects remain unknown. This study examines how these two types of attention training modulate neurological dysfunction in veterans with PTSD. A community sample of 46 combat veterans with PTSD participated in a randomized double-blinded clinical trial of ACT versus ABMT and 32 of those veterans also agreed to undergo resting-state magnetoencephalography (MEG) recordings. Twenty-four veterans completed psychological and MEG assessments at pre- and post-training to evaluate treatment effects. MEG data were imaged using an advanced Bayesian reconstruction method and examined using statistical parametric mapping. In this report, we focus on the neural correlates and the differential treatment effects observed using MEG; the results of the full clinical trial have been described elsewhere. Our results indicated that ACT modulated occipital and ABMT modulated medial temporal activity more strongly than the comparative treatment. PTSD symptoms decreased significantly from pre- to post-test. These initial neurophysiological outcome data suggest that ACT modulates visual pathways, while ABMT modulates threat-processing regions, but that both are associated with normalizing aberrant neural activity in veterans with PTSD. Highlights: PTSD is associated with neurophysiological aberrations across multiple networks. These activation differences can be partially reversed by attention training. Attention control training modulates visual pathways which are understudied in PTSD. Attention bias modification modulates threat-processing regions in PTSD.